Implementation Of PJOK Learning During The Covid-19 Pandemic Between Public Schools And Private Elementary Schools In Rejang Lebong Regency - Defliyanto Defliyanto; Tono Sugihartono; Edwin Hariansyah (Universitas Bengkulu, 2021)
This study aims to to find out the application of learning and the differences in the application of PJOK learning during the Covid-19 pandemic which was carried out by State and Private Schools at the SD level throughout Rejang Lebong Regency. This type of research is descriptive qualitative. The subjects of this study amounted to 60 people consisting of the Principal, Teachers and Students. The instruments and data collection techniques used in this study were observation, questionnaires, interviews and documentation. The data analysis technique used is descriptive analysis with percentages. The results showed that the implementation of PJOK learning during the Covid-19 pandemic related to the Semester Program, RPP and Learning Process at State Elementary Schools was in the Good category with a percentage of 70%, the Ministry of Education's Private Elementary School was in the Very Good category with a percentage of 81.66%, and Private Elementary Schools. The Ministry of Religion is in the Enough category with a percentage of 59%. Furthermore, the difference in the application of learning in public schools and private schools lies in the learning methods and media used by each elementary school unit.